Effectivity of Law Enforcement Towards Teenagers’ Brawl by Criminal Investigation Unit of East Jakarta Police Department - Muhamad Reza Pradana (Indonesian Journal of Police Studies, 2021)
East Jakarta Police Department has the right to do law enforcement in East Jakarta Region. The most frequent of violation of the law in East Jakarta is teenagers brawl, where the violation can be enforced by Criminal Investigation Unit of East Jakarta Police Department. This research had used several theory and concept, which are the effectivity theory, deterrent effect theory and law enforcement theory. On the other hand the concept that had been used are the investigation concept, children and teenager concept, children and teenager investigation concept, and the law violation concept. This research used the qualitative approach with field study method on the law enforcement that had been conducted by Criminal Investigation Unit of East Jakarta Police Department towards teenagers' brawl in East Jakarta. The writer collected data with observation within the implementation of law enforcement, interview with subjects, documents collecting from Criminal Investigation Unit of East Jakarta Police Department. From this research, the writer conclude that the implementation of law enforcement by Criminal Investigation Unit of East Jakarta Police Department towards the perpetrator of teenagers’ brawl can’t be fully objected by Criminal Procedure Law and the conviction can’t be entirely based on Criminal Law Code, because the object of the law enforcement is between 12 to 18 years old, it is directed by the National Law Code No. 11 of 2012 about The Criminal Justice System For Children and Teenager. Other than that, the act of law enforcement is considered not effective because it does not cause a deterrent effect towards the perpetrator of teenagers’ brawl cases number from 2018 to 2020.